Wolny Związkowiec . biuletyn Komitetu Strajkowgo HK, 19 December 1981 (godz. 16.00) - Wróbel, Mirosław; Janiak, Hanna; Gągalski, Aleksander (NSZZ "Solidarność" "Huta Katowice", 1981)
Creation and circulation: After introduction of the Martial Law on December 13, 1981 published underground. First published more than once a day as occupation edition, later irregularly. From issue no. 10(wrzesień 1989) published again legally